Relationship between the right to protest and the deliberative theories of democracy in the works of R. Gargarella (2008)
This text analyzes the theory of deliberative democracy from the standpoint of the Gargarella version and the articulation of the right to protest in cases where there is a deficit in the guaranties of rights. First, it begins from the deliberative concep